Patch testing with the European baseline series and 10 added allergens: Single‐centre study of 748 patients - Bizjak, Mojca; Adamič, Katja; Bajrovič, Nissera; Eržen, Renato; Jošt, Maja; Kopač, Peter; Košnik, Mitja; Lalek, Nika; Zidarn, Mihaela; Dinevski, Dejan (Contact dermatitis, 2022)
Background The European baseline series (EBS) of contact allergens is subject to change. An allergen is considered for inclusion when routine patch testing of patients with suspected contact dermatitis results in ≥0.5% prevalence rate. Objectives We aimed to determine the frequency of sensitizations to 30 EBS allergens and 10 locally added allergens. Additionally, we assessed the strength and evolution of reactions to all tested allergens and co‐reactivity of additional allergens. Methods Patch testing with our baseline series of 40 allergens was done in 748 consecutive adults. Tests were applied to the upper back and removed by patients after 48 h. Readings were done on Day 3 (D3) and D6 or D7 (D6/7). Positive reactions fulfilled the criteria of at least one plus (+) reaction. A retrospective analysis was done. Results Eight allergens not listed in the EBS had ≥0.5% prevalence rate (i.e., cocamidopropyl betaine, thiomersal, disperse blue mix 106/124, 2‐bromo‐2‐nitropropane‐1,3‐diol, diazolidinyl urea, propylene glycol, Compositae mix II and dexamethasone‐21‐phosphate), and 16.6% of positive reactions would have been missed without D6/7 readings. Conclusion We propose further studies to evaluate whether cocamidopropyl betaine, disperse blue mix 106/124, 2‐bromo‐2‐nitropropane‐1,3‐diol, diazolidinyl urea and Compositae mix II need to be added to the EBS. Our study results suggest that cocamidopropyl betaine 1% aq., disperse blue mix 106/124 1% pet., 2‐bromo‐2‐nitropropane‐1,3‐diol 0.5% pet., Compositae mix II 5% pet. and diazolidinyl urea 2% pet. may need to be added to the European baseline series of patch test allergens.